Identifying Interesting Sceneries and Objects in A Tropic Forest Through Visitors Employed Photography - Akhmad Arifin Hadi; Andi Gunawan; Tsuyoshi Honjo; Katsunori Furuya (Jurnal Ilmu Lingkungan, 2024)
Tropical Forest is a unique forest landscape character composed of vegetation with various altitude strata combined with other biotic and abiotic landscape elements. The combination of landscape objects produces a landscape character that is visually attractive to visitors. There are few references to forest sceneries and objects of interest to forest visitors, even though this information is important for forest tourism. This study identified tropical forest sceneries and objects of interest to forest visitors through photographs taken by visitors. The method used is Visitors' Employed Photography (VEP) combined with GPS tracking and artificial intelligence Google Clouds Vision API. In this VEP method, we invited 41 respondents to walk in the "Situ Gede Forest " and directly photograph interesting objects in the field. We obtained 1,206 photos from respondents containing the scenery and objects of the "Situ Gede Forest" and the location of the photo-taking points. The photos were labeled via Google Cloud's Vision API and clustered based on the Photo's label into 15 photo clusters using R Statistics software. The grouping results identified three sceneries and objects that interested the respondents: "View to the standing of trees inside the forest, woodland, or jungle," "Forest scenery with recreational activities and zoo," and "Body of water, edge of the body of water, waterway, and trees." Information on the three characteristics of tropical forest landscapes is beneficial in tropical forest management activities, where landscapes with these three types must be conserved and preserved in the interest of sustainable tourism forest.